Bahaya Stunting Dan Upaya Penanggulangan Stunting Melalui Penggunaan Tablet Tambah Darah Pada Remaja Putri - Fitrawan, La Ode Muhammad; Yamin, Yamin; Tamrin, Andita Septiani; Pascayantri, Asniar; Sholiha, Desi Nur; Ramadhani, Faadhilah; Sani, Mega Permata; Febriani, Rani; Ningsi, Wa Ode Fajar (Jurnal Mandala Pengabdian Masyarakat, 2024)
Stunting describes chronic malnutrition status during growth and development since early life. There are many factors that can cause stunting, one of which is a lack of Fe intake in teenagers. Insufficient iron intake can cause stunted growth which, if it occurs for a long time, can cause stunting. This counseling aims to provide education to teenagers and how to prevent it. The method used in this activity was direct lectures to young women at the Abdurrahman bin Auf Islamic Boarding School. This activity received a good response from the Islamic Boarding School and enthusiasm from the participants. Participants can understand the material provided and gain insight and are also expected to contribute to reducing stunting rates in Indonesia.